The 5th Generation of Mobile Internet - Jintong Lin; Xiaodong Xu (Dianxin kexue)
The development history of the optical fiber communication，internet，mobile communication and internet of things were reviewed. The features，typical system performances and key technologies of above systems and networks were analyzed. Based on these，the 5th generation of mobile internet was brought forward with the backgrounds，features，key performance indicators and candidate technologies. Parts of key technologies for supporting the 5th generation of mobile internet were analyzed in detai1. The future research directions of above technologies were also discussed. Finally，the related standard activities for the 5th generation of mobile internet were introduced.